The Clinical Application of Mealtime Whey Protein for the Treatment of Postprandial Hyperglycaemia for People With Type 2 Diabetes: A Long Whey to Go - Smith, Kieran; Bowden Davies, Kelly A.; Stevenson, Emma J.; West, Daniel J. (Frontiers in Nutrition, 2020)
Mitigating postprandial hyperglycaemic excursions may be effective in not only enhancing glycaemic control for people with type 2 diabetes but also reducing the onset of diabetes-related complications. However, there are growing concerns over the long-term efficacy of anti-hyperglycaemic pharmacotherapies, which coupled with their rising financial costs, underlines the need for further non-pharmaceutical treatments to regulate postprandial glycaemic excursions. One promising strategy that acutely improves postprandial glycaemia for people with type 2 diabetes is through the provision of mealtime whey protein, owing to the slowing of gastric emptying and increased secretion of insulin and the incretin peptides. The magnitude of this effect appears greater when whey protein is consumed before, rather than with, a meal. Herein, this dietary tool may offer a simple and inexpensive strategy in the management of postprandial hyperglycaemia for people with type 2 diabetes. However, there are insufficient long-term studies that have investigated the use of mealtime whey protein as a treatment option for individuals with type 2 diabetes. The methodological approaches applied in acute studies and outcomes reported may also not portray what is achievable long-term in practice. Therefore, studies are needed to refine the application of this mealtime strategy to maximize its clinical potential to treat hyperglycaemia and to apply these long-term to address key components of successful diabetes care. This review discusses evidence surrounding the provision of mealtime whey protein to treat postprandial hyperglycaemia in individuals with type 2 diabetes and highlights areas to help facilitate its clinical application.